2017
DOI: 10.18632/oncotarget.18463
|View full text |Cite
|
Sign up to set email alerts
|

TAp63γ and ΔNp63γ are regulated by RBM38 via mRNA stability and have an opposing function in growth suppression

Abstract: The p63 gene is expressed as TAp63 from the P1 promoter and as ΔNp63 from the P2 promoter. Through alternative splicing, five TA and five ΔN isoforms (α-ε) are expressed. Isoforms α-β and δ share an identical 3’ untranslated region (3’UTR) whereas isoform γ has a unique 3’UTR. Recently, we found that RBM38 RNA-binding protein is a target of p63 and RBM38 in turn regulates p63α/β expression via mRNA stability. However, it is uncertain whether p63γ has a unique biological activity and whether p63γ is regulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Clinically, p63 has value in identifying malignancy and for tumour classification, and isoform‐specific ΔNp63 antibodies are superior to assessing total p63 in many situations (reviewed in ref 249). In addition, although not well studied in clinical material, TAp63 provides prognostic information [15,18,249–251] and requires more study in lymphomas and lymphocytes (including tumour‐infiltrating lymphocytes) to understand its prognostic impact and opportunities for therapy. Advances in understanding p63 isoforms and their regulation will inevitably lead to new diagnostic, prognostic and therapeutic opportunities for cancer and other pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, p63 has value in identifying malignancy and for tumour classification, and isoform‐specific ΔNp63 antibodies are superior to assessing total p63 in many situations (reviewed in ref 249). In addition, although not well studied in clinical material, TAp63 provides prognostic information [15,18,249–251] and requires more study in lymphomas and lymphocytes (including tumour‐infiltrating lymphocytes) to understand its prognostic impact and opportunities for therapy. Advances in understanding p63 isoforms and their regulation will inevitably lead to new diagnostic, prognostic and therapeutic opportunities for cancer and other pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that Rbm38 decreases p63␣/␤ mRNA stability by binding to AU/Urich elements in their 3ЈUTR (12,13). By contrast, Rbm38 enhances p63␥ mRNA stability by binding to a GU-rich element in p63␥ 3ЈUTR, which has a sequence different from that in p63␣/␤ 3ЈUTR (14). In addition, we found that Rbm38 interacts with p53 mRNA and represses p53 translation (15).…”
mentioning
confidence: 57%
“…pcDNA3 vector expressing GFP was generated as described previously (20). pcDNA3 vector expressing HA-tagged p53-R175H was generated as described previously (14). The pcDNA3 p53-R175H-3ЈUTR reporter was generated by cloning p63 3ЈUTR into pcDNA3-HA-p53-R175H downstream of p53-R175H-CDS.…”
Section: Plasmidsmentioning
confidence: 99%
“…The underlying mechanisms of RNPC1 in the process of tumors may be due to its stabilizing effect on mRNA of oncogenes or tumor suppressors. For example, RNPC1 can regulate biological processes by binding and stabilizing the mRNA of p21 [45], p73 [46], Hu antigen-R (HuR) [45,47] and macrophage inhibitory cytokine-1 (MIC-1) [48], Zonula occludens-1 (ZO-1) [49], PTEN [25,29] (phosphatase and tensin homolog gene on chromosome 10), estrogen receptor (ER) [43], and progesterone receptor (PR) [50] or by binding to the mRNAs of p63 [51][52][53][54], c-myc [55], murine double minute-2 (MDM2) [56],and p53 [25] and mediating the decrease in the mRNA levels. In our previous study, we de ned thatAURKB was the targeted gene of RNPC1 by RIP-Seq [29].…”
Section: Discussionmentioning
confidence: 99%